Revija Znamenje v Grmičevem ustvarjalnem opusu - Reher, Srečko (Časopis za zgodovino in narodopisje, 2023)
The founding and content focus of Znamenje journal, founded in 1971 by three central Catholic intellectuals of the time, Vekoslav Grmič, Edvard Kocbek and Stanko Cajnkar, coincided with a number of changes in the political, cultural, and economic spheres of both Yugoslavia at the time and the Catholic Church after the Second Vatican Council. Grmič contributed to Znamenje journal from its first issue until his death in 2005. He was its editor-in-chief from the 17th to the 20th editions, the editor responsible from the 16th to the 20th editions, and was also involved in its committees. During the forty-two years of its publication (from 1971 to 2012), thanks to him, the journal was not only given tone by renowned local theologians and intellectuals – whether believers, non-believers, or otherwise – but was also enriched by the translations of the world’s leading theologians and scholars in a wide range of scientific fields, critical assessments of traditional theology, religious practices, the Church’s institutional religiosity, social, political and cultural developments in Europe and around the world, and opening up the horizons of new contextual theologies that answered concrete questions in the light of faith.
Keywords: Cerkev; družbene razmere; Grmič, Vekoslav; krščanstvo; kultura; teologija; Znamenje (periodična publikacija)